Why the Furor about Polio? - Samuel Amo-Tachie (University Library System, University of Pittsburgh, 2023)
Poliomyelitis is one of such diseases as measles and dracunculiasis that can be eradicated, because it meets the criteria for eradicable diseases: being infectious, having humans as major host, effective vaccines or treatment available for their control, and the availability of political and financial support for the eradication efforts. Ghana, with the rest of the world has already come far in the fight against polio, by reducing its incidence drastically (to zero as of now). The disease can only be prevented but not reversible, once infection results in paralysis and leaves victims permanently maimed, almost invariably reducing their quality of life. The recent outbreak (caused by a circulating vaccine-derived virus of the type 2 strain) was a call to pay more attention to the disease in order to realize the global aim of its elimination. All the attention needed by the disease is center around vaccination, which indeed was the tool used in combating the outbreak that ensued in Ghana.